Concentration of stromal cell‐derived factor‐1 (SDF‐1/CXCL12) in the follicular fluid is associated with blastocyst development. (28th November 2018) - Nishigaki, Akemi; Tsuzuki‐Nakao, Tomoko; Kido, Takeharu; Kida, Naoko; Kakita‐Kobayashi, Maiko; Murata, Hiromi; Okada, Hidetaka
Abstract: Purpose: To study the association between stromal cell‐derived factor‐1 (SDF‐1/CXCL12) and vascular endothelial growth factor (VEGF) concentrations in individual human ovarian follicles and IVF outcomes. Methods: Concentrations of SDF‐1 and VEGF in 261 follicular fluid samples were measured with enzyme‐linked immunosorbent assay. IVF outcome parameters were included in fertilization rate, cleavage rate, embryo morphology on day 3, and blastocyst morphology on day 5. Results: The follicular concentration of SDF‐1 and VEGF was not significantly associated with fertilization and cleavage outcome, and embryo morphology. The rates of full blastocysts and good‐quality blastocysts were significantly higher in follicles with an SDF‐1 concentration of 275‐350 pg/mL than in the follicles with SDF‐1 concentrations of <200 and ≥350 pg/mL ( P <  0.05). The follicular concentration of VEGF was not associated with the blastocyst morphology. Conclusion: Our findings showed that follicular concentration of SDF‐1, and not VEGF, may be a valuable biochemical marker of blastocyst development.